The Effect Of Static Stretching Exercise Olah Tubuh In Reducing Delayed Onset Muscle Sorees Of The Gastrocnemius Muscle In Dancers In UKM Sangsekarta - Nabila Randy Dhiyanisa; Rahmanto, Safun; Imanurrohmah, Zidni; Faradilla Rahim, Anita; Aini Rahmawati, Nurul (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Preserving culture can be done by participating in being part of a dancer. In dancing activities, especially Javanese dance, has 3 main elements, namely wiraga (harmony of motion), wirama (harmony of rhythm), and wirasa (harmony of taste). Dancers need power and energy for the movements they make, in order to achieve the main element of wiraga. Dancing with the movement of the human body allows that dance activities are related to muscles so that it will allow the occurrence of musculoskeletal disorders (MSDs) in dancers including one of which is Delayed Onset Muscle Soreness (DOMS). The muscle that is most susceptible to DOMS is the Gastrocnemius muscle. DOMS can be reduced one way is to use the static stretching exercise intervention method. This study aims to determine the effect of static stretching exercise in reducing Delay Onset Muscle Sorenes of the gastrocnemius muscle in dancers at UKM Sangsekarta. This study aims to determine the effect of static stretching exercise in reducing Delay Onset Muscle Sorenes of the gastrocnemius muscle in dancers at UKM Sangsekarta. This research was conducted with a quantitative approach, and applied a pre-experimental design one group pretest-postest and 27 respondents were found. Static stretching body exercise is an independent variable. As for the dependent variable, namely Delayed Onset Muscle Soreness of the gastrocnemius muscle. The results of this study obtained pretest and postest values of 0.006 (p>0.05) and 0.006 (p>0.05). It can be concluded from the results of the normality test that it shows abnormal distribution, while the hypothesis test using the Wilcoxon test obtained a p value of <0.000 less than 0.05. It can be concluded that there is an effect of static stretching exercise on reducing gastrocnemius muscle DOMS in dancers at UKM Sangsekarta.